Teaching and Learning of Calculus - Bressoud, David; Ghedamsi, Imène; Martinez-Luaces, Victor; Törner, Günter (ICME-13 Topical Surveys,, 2016)
This survey focuses on the main trends in the field of calculus education. Despite their variety, the findings reveal a cornerstone issue that is strongly linked to the formalism of calculus concepts and to the difficulties it generates in the learning and teaching process. As a complement to the main text, an extended bibliography with some of the most important references on this topic is included. Since the diversity of the research in the field makes it difficult to produce an exhaustive state-of-the-art summary, the authors discuss recent developments that go beyond this survey and put forward new research questions.